PENERAPAN KINESIO TAPING LEBIH EFEKTIF DARIPADA BANDAGE ELASTIC PADA INTERVENSI LATIHAN STABILISASI TERHADAP PENURUNAN NYERI AKIBAT CEDERA LIGAMEN KOLATERAL MEDIAL SENDI LUTUT - -, Syamsyul; Handari Adiputra, Luh Made Indah Sri; Lesmana, S Indra (Sport and Fitness Journal; Volume 3, No.3, 2015, 2015)
Medial collateral ligament knee joint injury is one of movement disorders which causes impaired mobility and function that inhibits daily activities. Pain and disability will be increasing with the emergence of fatigue and atropism of muscles functioning as dynamic stabilizer. Pain commonly occurs on a condition of medial collateral ligament knee joint injury type I, in acute and chronic phase. The purpose of this study to determine the effectiveness of the application of Kinesiotaping and elastic Bandage on intervention stabilization exercises to decrease pain caused by injury to the medial collateral ligament of the knee joint.This study was experimental with randomized pre and post test group design which aimed to learn about causal phenomena by giving treatment to the study objects. The study was carried out in Sport Health Clinic KONI Kota Langsa starting March to May 2015. The subjects of study were 20 patients who were classified into two groups, 10 subjects of treatment group I given kinesiotaping application and 10 subjects of treatment group II given elastic bandage application. The measuring tool of VAS (Visual Analogue Scale) was used to find out any pain reduction. The results of study showed that group I and II indicating pain decrease with value of p = 0.008 (p<0.05) and p = 0.000 (p<0.005) respectively. Statistical analysis also showed a significant difference on both groups. Application of technique on group I was as effective as on group II to reduce pain due to medial collateral ligament knee joint injury (p>0.05). From the above findings can be summarized that applications of both kinesiotaping and elastic bandage on intervention of stabilization exercise are effective to reduce pain due to medial collateral ligament knee joint injury.
Keywords: Kinesiotaping, Elastic Bandage, Intervention of stabilization exercise, Pain, Ligament injury